Functional appliance treatment assessed using the PAR Index - Wijayaratne Dilshan; Harkness Michael; Herbison Peter (Sciendo, 2000)
The aims of this study were, first, to determine in children with Class II, division 1 malocclusions treated with functional appliances if, according to the Peer Assessment Rating (PAR) Index, lower incisor proclination affects the assessment of treatment outcome; and, second, to evaluate the effectiveness of such treatment before and after adjustment for any lower incisor proclination.